Modular robot manipulator - HODGE; STEVEN W (1988)
A modular robotic remote manipulator is disclosed. The manipulator utilizes a base module, any number of generally identical but appropriately sized articulating modules, extender modules as may be needed, and an end effector module to accommodate the task assigned to the manipulator. The articulating modules are constructed to afford three different motions about three different axes which intersect at a common point lying between the input end and the output end of the module to effect a range of possible motion for the module output which defines an imaginary sphere. This module is also constructed to provide a separate rotary torque through the output coupling to the next module. The couplers for interconnecting the modules utilize toggle operated spool shaped locks. An end effector or gripper employs a rotating shaft and follower connected through a cable and pulley arrangement to operate the gripper jaws.